2016
DOI: 10.1002/jqs.2832
|View full text |Cite
|
Sign up to set email alerts
|

Isostatic compensation of Quaternary vertical crustal motions: coupling between uplift of Britain and subsidence beneath the North Sea

Abstract: New data from offshore and onshore regions confirm the view that the Quaternary uplift of Britain and subsidence beneath the North Sea are coupled, mediated by lower‐crustal flow induced by the lateral pressure gradient caused by climate‐driven surface processes. Most measured onshore uplift rates, in both upland and lowland localities, are only applicable since the Mid‐Pleistocene Revolution; beforehand, generally lower rates prevailed. Earlier (?Oligocene–Pliocene) phases of uplift and subsidence had typical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 107 publications
(257 reference statements)
0
35
0
Order By: Relevance
“…Westaway (, ) and Green et al () have suggested that Neogene exhumation was significant, driven by lower‐crustal flow due to rapid subsidence and deposition in the North Sea. Our study provides little clear evidence for a resolvable regional Late Cenozoic cooling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Westaway (, ) and Green et al () have suggested that Neogene exhumation was significant, driven by lower‐crustal flow due to rapid subsidence and deposition in the North Sea. Our study provides little clear evidence for a resolvable regional Late Cenozoic cooling.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is little consensus on (i) the amount, timing, and spatial variability of rock uplift and denudation associated with the arrival of the proto‐Iceland mantle plume (Cogné et al, ; Davis et al, ; Green, , ; Lewis et al, ; Saunders et al, ); (ii) how it is apportioned between permanent and transient uplift (Cogné et al, ; Hartley et al, ; Tiley et al, ; White & Lovell, ); and (iii) the contribution of large scale plate tectonic processes in the Neogene (Hillis et al, ; Holford et al, ; Stoker et al, ) or lower‐crustal flow in response to lithostatic loading and subsidence in the adjacent offshore basins (Green et al, ; Westaway, , ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the age of the broad topographic expression of central and southern Scotland is likely to be of Late Miocene age, corresponding to a widespread unconformity that extends across much of Britain, the North Sea and Fennoscandia (Clausen & Huuse ; Clausen et al . ; Westaway , ; Lee et al . ).…”
Section: Regional Geological Backgroundmentioning
confidence: 99%
“…Studies into the burial history of the Carboniferous rocks that are currently at the ground surface suggest that they only came close to the surface in the Neogene; prior to this they were buried up to 2.5 km deep (Vincent et al 2010). Therefore, the age of the broad topographic expression of central and southern Scotland is likely to be of Late Miocene age, corresponding to a wide spread unconformity that extends across much of Britain, the North Sea and Fennoscandia (Clausen & Huuse 1999;Westaway 2010Westaway , 2017Lee et al 2017). No pre-Quaternary saporolites or sediments have been found in the Midland Valleyof Scotland (Cameron & Stephenson 1985;M.…”
Section: Pre-quaternary Evolution Of Central and Southern Scotlandmentioning
confidence: 99%
“…The papers by Lamb et al . (), Buckley () and Westaway () tackle a number of issues regarding the Early to Middle Quaternary history of the North Sea (Fig. ).…”
Section: Introduction − the Quaternary Of The North Sea Basin And Itsmentioning
confidence: 99%